The bumpy road toward low-energy urban mobility: Case studies from two UK cities - Schwanen, T (MDPI, 2015)
Cities are increasingly seen as the places where innovations that can trigger a sociotechnical transition toward urban mobility are emerging and maturing. Processes such as peak car, rail renaissance and cycling boom manifest themselves particularly in cities, and success stories of cities experimenting with specific types of low-energy mobility abound in the academic literature. Nonetheless, innovation is known to be a precarious process requiring favorable circumstances. Using document analysis and in-depth interviews, this study examines the nature of low-energy innovation in the everyday mobility of people in two UK cities with favorable conditions for a transition away from fossil fuels—Brighton and Oxford. It shows that clear differences exist between the two cities in the sorts of innovation that emerge and diffuse as a result of path dependencies, local politics, and financial support from supra-local governments and agencies. While low-energy mobility currently has substantial momentum in both cities, the majority of low-carbon innovations in urban mobility are incremental rather than radical in nature, and their future is often imbued with uncertainty. The autonomy of small- and medium-sized cities as agents in bringing about transformational change toward low-energy urban mobility should not be overestimated.